Physical Modeling of Greywater into Clean Water with Fragrant Root (Vetiveria Zizanoides) in View of pH,Turbidity - Wulandari, Lies Kurniawati; Mundra, I Wayan; Hardianto, Hardianto; Munasih, Munasih (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
Vetiver grass or what is locally known as vetiver grass, is a type of aquatic plant that has long grown wild so it is very easy to find. It turns out that the potential of vetiver grass can not only be used as a handicraft and ornamental plant, but can also be used as a waste water remediation agent. The method used is to plant vetiver roots in soil submerged in tilapia pond waste water with variations in discharge, number of vetiver stems and time. The results of the description of the turbidity parameters show that with a total of 150 vetiver stems and each additional water discharge at different residence time periods will be able to reduce the turbidity value and increase the pH so that the quality of the waste water discharge increases. It can be concluded that: the initial pH of 7.30 increased to 7.90 and was standard (6.5 – 8.5) with a residence time of 7 days. And the initial turbidity of 119 decreased to 5.44 NTU and standard (<3 NTU), with a remaining time of 7 days. So, the residence time must be longer in order to meet the specified standards.